Retrieving functional pathways of biomolecules from single-particle snapshots - Ali Dashti (Nature Portfolio, 2020)
There is a great interest in retrieving functional pathways from cryo-EM single-particle data. Here, the authors present an approach that combines cryo-EM with advanced data-analytical methods and molecular dynamics simulations to reveal the functional pathways traversed on experimentally derived energy landscapes using the ryanodine receptor type 1 as an example.